Quantification of methane emission rate from oil and gas wells in Romania using ground-based measurement techniques - Korbeń, Piotr; Jagoda, Pawel; Maazallahi, Hossein; Kammerer, Johannes; Necki, Jaroslaw M.; Wietzel, Julia B.; Bartyzel, Jakub; Radovici, Andrei; Zavala-Araiza, Daniel; Röckmann, Thomas; Schmidt, Martina (Elementa, 2022)
The ROMEO campaign (ROmanian Methane Emissions from Oil and gas) focused on measurements of methane (CH4) emission rates from oil and natural gas (O&G) production in Romania. The campaign took place in October 2019 and covered the southern part of Romania around the cities Bucharest, Ploiesti, Pitesti, and Craiova. This study presents emission rates calculated from mobile in situ measurement of CH4 and wind measurements using the Other Test Method 33a from U.S. Environmental Protection Agency and the Gaussian Plume Method. These methods were used to determine emission rates from 112 O&G well sites and other production-related facilities. Estimated mean CH4 emission rate with a 95% confidence interval equals 0.49 [0.35, 0.71] kg CH4 h-1 per site; 10% of all quantified sites account for 56% of the estimated emission rates. In addition, more than 1,000 O&G sites were visited for a qualitative ???screening??? (CH4 detection without quantification). Analysis of the screening data shows that 65% of the sites emitted methane at detectable rates. The CH4 emission rates obtained during the ROMEO campaign are comparable to the methane emission rates in study carried out in other Romanian regions.